Uso de sig e fotografias aéreas na determinação de conflitos na rede de drenagem na bacia experimental do Rio Pardo - Nascimento, Flávia Meinicke; de Barros, Zacarias Xavier [UNESP]; de Barros, Bruna Soares Xavier [UNESP]; Campos, Sérgio [UNESP]; Rodrigues, José Guilherme Lança (My University, 2012)
This study aimed to detect and evaluate potential conflicts in the land use along the Rio Pardo's tributaries and sub-tributaries from its source which is in Pardinho, SP to the water capture system by the Basic Sanitation Company located in Botucatu, SP. It was used 2005 colored aerial photos, taking as a tool for assessing the Geographical Information System - IDRISI Andes. The results showed that the riparian forests were substituted predominantly by pastures, which is called conflict. In other words, the 1590.82ha of environmental preservation areas (PPA's) that should be protected by riparian forests and meadows (41.51%) in 2005, were used as pastures, being in conflict with the legislation. The aerial pictures associated to SIG-Idrisi proved to be efficient tools in mapping the area and monitoring the environmental impacts.
The use of sig and aerial photographs determining conflicts of the drainage net in river pardo experimental basin
Keywords: Conflict of land use; Geoprocessing; Remote sensing; aerial photography; drainage network; GIS; land use conflict; remote sensing; tributary; Brazil; Pardinho River; Rio Grande do Sul